2014
DOI: 10.1111/myc.12181
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the ITS rDNA regions for differentiating strains of the Trichophyton mentagrophytes complex in Sfax‐Tunisia

Abstract: The Trichophyton mentagrophytes complex is the main cause of superficial mycoses in humans and animals. Molecular research has provided useful insights into the taxonomy of this complex to overcome the challenges with conventional diagnostics. The aim of this study was to identify, type and differentiate anthropophilic and zoophilic species of the T. mentagrophytes complex. Sixty clinical samples identified as T. mentagrophytes by morphological characteristics were isolated using polymerase chain reaction-rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The T. interdigitale isolates herein identified presented the same restriction pattern on ITS-RFLP and were grouped together with the anthropophilic ones in the phylogenetic analysis. A recent report with 60 clinical isolates of dermatophytes showed that the most of them belonged to the anthropophilic variant of T. mentagrophytes complex [35].…”
Section: Discussionmentioning
confidence: 99%
“…The T. interdigitale isolates herein identified presented the same restriction pattern on ITS-RFLP and were grouped together with the anthropophilic ones in the phylogenetic analysis. A recent report with 60 clinical isolates of dermatophytes showed that the most of them belonged to the anthropophilic variant of T. mentagrophytes complex [35].…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported six sequence types. Drira et al . used scheme, identical to that by Heidemann et al .…”
Section: Discussionmentioning
confidence: 99%
“…The strain RCPF‐1278 originated from the case of tinea pedis. There are no III* sequences known from this location, and we assigned this sequence to the type III because of its origin. Our isolates RCPF‐1261, RCPF‐1425 and RCPF‐1640 could be easily attributed to the Heidemann's sequence type IV, but all lacked two additional polymorphisms, transversion G22C and insertion 217insA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations